Developing Syllabus and Reading Teaching Materials for BIPA A1 Based on Deductive Approach - Siti Ayu Ningsih; Liliana Muliastuti (Indonesian Language and Literature Education Study Program and LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2019)
This study aims to describe: 1) the development of reading syllabus for BIPA level A1 using deductive approach in D’Royal Moroco Integrative Islamic Elementary School, and 2) the development of reading teaching material for BIPA level A1 using deductive approach in D’Royal Moroco Integrative Islamic Elementary School. The method used in this research was research and development method. Based on the observations, documents analysis, interviews, and tests, during need analysis period, can be elaborated that the school did not have any teaching materials for BIPA. While the school had quite a lot of BIPA students mostly at A1 level. This situasions need immediate action of developing syllabus and reading teaching material for BIPA at A1 level. Due to the target of the users for this syllabus and teaching material, deductive approach can be used to developing the syllabus and the reading teaching material of BIPA A1 since the children learn more effectively by imitating the examples, and deductive approach suits that needs. By following the deductive approach, the syllabus should contains the role of teacher and students while the teaching material should have: 1) begins with the concept introduction, 2) followed by relevant examples, and 3) contains of adequate practice. It is also should containing relevant and interesting illustrations.